Determination of the sequences of protein-derived peptides and peptide mixtures by mass spectrometry. - Morris,HR; Williams,DH; Ambler,RP (Biochem J, 1971)
Micro-quantities of protein-derived peptides have been converted into N-acetylated permethyl derivatives, and their sequences determined by low-resolution mass spectrometry without prior knowledge of their amino acid compositions or lengths. A new strategy is suggested for the mass spectrometric sequencing of oligopeptides or proteins, involving gel filtration of protein hydrolysates and subsequent sequence analysis of peptide mixtures. Finally, results are given that demonstrate for the first time the use of mass spectrometry for the analysis of a protein-derived peptide mixture, again without prior knowledge of the protein or components within the mixture.